EXPLORING STRATEGIES FOR ENHANCING PARENTAL PARTICIPATION AND INFLUENCE IN SCHOOL DECISION-MAKING PROCESSES: A CASE OF PRIMARY SCHOOLS - Saltiel Khololo Collen Mataboge (CV. RADJA PUBLIKA, 2024)
The purpose of this conceptual paper is to explore strategies for enhancing parental participation and influence in school decision-making processes, focusing specifically on primary schools. The main research question guiding this study is: How can parental participation and influence in school decision-making processes be effectively enhanced? This qualitative study draws upon a comprehensive review of scholarly books and articles, forming the cornerstone of the research. Data collection is conducted through qualitative methods aligned with the interpretive paradigm, allowing for an in-depth exploration of parental perspectives and experiences in school decision-making. Findings from this study highlight the importance of fostering meaningful partnerships between schools and parents to promote collaborative decision-making. Parents' active involvement in decision-making processes not only enhances school governance but also contributes to improved student outcomes and overall school effectiveness. The significance of this study lies in its potential to inform the development and implementation of strategies aimed at enhancing parental participation and influence in school decision-making processes. When recognizing parents as valuable stakeholders in the education system, schools can leverage their insights, expertise, and diverse perspectives to make more informed and inclusive decisions. Educators, policymakers, and school leaders are urged to foster a culture of partnership and collaboration between schools and parents. These recommendations emphasize the importance of communication, transparency, and meaningful engagement to ensure that parents are empowered to play an active role in shaping the educational experiences of their children.